THE CORRELATION BETWEEN THE USE OF VISUAL MEDIA AND STUDENTS' PARTICIPATION IN ENGLISH INSRUCTIONAL PROCESS - Hafidzah, Kurrota (2016)
The objectives of this study are to discover what the students' participation levels are when visual media is utilized and whether there is a significant correlation between the use of visual media and the students' participation. It also intends to measure the extent to which the use of visual media predicts students' participation in classroom. Correlational research design was used to obtain the data, where observation sheet and students participation rubric adapted from Valley Central High School and teach-nology.com was used to assess students' participation and questionnaire was administered to obtain the data of visual media. The data were gathered from 90 eighth grade students in one of Junior High School in Bandung. The result showed that most students participated well. Correlational analyses revealed a positive correlation between the use of visual media and students' participation, which is statistically significant (r = .577, n = 90 p<0.01). It means that the use of visual media has a correlation with students' participation in classroom.;--- Tujuan dari penelitian ini adalah untuk menemukan level partisipasi siswa di kelas ketika media visual digunakan dan mengetahui apakah ada hubungan yang signifikan antara pengunaan media visual dengan partisipasi siswa di kelas. Penelitian ini juga bertujuan untuk mengukur seberapa luas pengunaan media visual memprediksi partisipasi siswa di kelas. Desain penelitian yang dilakukan untuk mengumpulkan data adalah penelitian korelasi, dimana instrument yang digunakan adalah lembar observasi dengan rubrik penilaian yang diadaptasi dari Valley Central High School dan www.teach-nology.com untuk menilai partisipasi siswa dikelas dan kuesioner untuk menilai penggunaan media visual di kelas. Sebanyak 90 siswa kelas VIII di salah satu SMP di Bandung dipilih sebagai sampel penelitian. Hasil penelitian menunjukkan bahwa secara umum siswa berpartisipasi dengan baik selama proses pembelajaran menggunakan media visual. Analisis korelasi menunjukkan bahawa adanya hubungan yang positif dan signifikan (r = .577, n = 90 p<0.01)antara penggunaan media visual dan partisipasi siswa di kelas. Hal ini berarti bahwa penggunaan media visual di kelas selama prosess pembelajaran bahasa Inggris memiliki hubungana dengan partisipasi siswa di kelas.